Features of marketing tourism guidance (guiding children and teenagers) in the treatise on rights by Imam Al-Sajjad, peace be upon him - Dheyaa Radhi Kadhim (Peerian Journals Publishing, 2024)
Reading is based on the fragrant scientific human biography of Imam Al-Sajjad, peace be upon him It reveals to everyone that it is one of the pillars of piety, knowledge and Islamic thought In addition to that journey that he accompanied with his father and grandfather He spent it in an educational, moral, and scientific manner. Therefore, Imam Al-Sajjad, peace be upon him, placed it in his message about rights Which we will discuss, which refers to (features of marketing the tourism guidance process) An integrated curriculum for high Islamic life With the features of morals and rules of society As his message, may God Almighty’s prayers be upon him, occupied an important place in scientific circles for study and explanation Then it became one of the most important letters and writings dealing with human rights. Tourist guidance is a marketing process of great importance in transferring civilization to the nation and its elevation and its advancement according to a system with moral content based on purposeful foundations and standards We can say that this process is carried out according to the behavioral path It will lead to the eminence and elevation of this profession, because it is self-evident that this profession derives those values through what has enriched the Islamic world with thought, science, and morals. The tourist atmosphere is full of human movement, which is interspersed with those humanitarian actions that benefit people This is what tourism scholars have emphasized in their attempt to market these features for the purpose of reforming those magazines that would regulate the course of the tourism process Not only that process, but it is also suitable for other fields (political, economic, ethical, educational). Thus, an attempt is made to remove all manifestations of intellectual deviation and behavioral decadence that result from these human interests The tourism guiding process runs regularly and is free of any obstacles or problems.
Keywords: Marketing; Tour Guiding; Rights